1990
DOI: 10.1088/0953-2048/3/5/004
|View full text |Cite
|
Sign up to set email alerts
|

Y-Ba-Cu-O superconducting films grown on (100) magnesia and sapphire substrates by a melt growth method without crucible

Abstract: Superconducting Y-Ba-Cu-0 films were successfully prepared by a melt growth method without crucible on (100) MgO and sapphire substrates using a Ba,Cu,O,, flux. It was found that without a Y,BaCuO, (211) buffer layer, film formation is not feasible due to a wetting problem. The 21 1 layer reacts with the melt and is partly converted to theYBa,Cu,O, (123) film. The 123 film thickness is f to 3 that of the former 211 layer, whose quality in turn dominates the surface structure of the 123 film. The degree of pref… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

1997
1997
2013
2013

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…Moreover, the divergence of the crystallographic properties at the interface between YBCO and the commonly available substrates, as well as the difficulty in obtaining chemical and structural properties compatible with the YBCO superconductor, constitute a great motivation to produce new optimal materials for this application. For example, MgO, the widely utilized substrate for YBCO thin films, produces an interlayer of barium salt at the YBCO/MgO interface when the processing temperature is above 700 °C 5 . Another extensively used substrate for YBCO, LaAlO 3 , exhibits an excellent lattice coupling but it has the disadvantage of being available only as twinned single-crystal 6 .…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the divergence of the crystallographic properties at the interface between YBCO and the commonly available substrates, as well as the difficulty in obtaining chemical and structural properties compatible with the YBCO superconductor, constitute a great motivation to produce new optimal materials for this application. For example, MgO, the widely utilized substrate for YBCO thin films, produces an interlayer of barium salt at the YBCO/MgO interface when the processing temperature is above 700 °C 5 . Another extensively used substrate for YBCO, LaAlO 3 , exhibits an excellent lattice coupling but it has the disadvantage of being available only as twinned single-crystal 6 .…”
Section: Introductionmentioning
confidence: 99%
“…The presence of superstructural lines in the XRD pattern (figure 1) indicates the ordering of the basic ABO 3 perovskite unit cell in BLHO material. DTA analysis of BLHO material showed that there is no phase transition up to a temperature of 1200 • C. The sintered density of BLHO measured by the Archimedes method is ∼97% of the calculated theoretical density and the room temperature resistivity of BLHO is ∼10 10 cm. The electrical resistivity and density of the humidity treated BLHO samples measured after drying were the same as that of the sintered sample indicating that BLHO is highly stable under atmospheric conditions.…”
Section: Resultsmentioning
confidence: 84%
“…However, MgO forms an interlayer of barium salt at the YBCO-MgO interface if the processing temperature is above 700 • C and reduces the superconducting transition temperature of the YBCO film considerably [9,10]. The Bi(Pb)-Sr-Ca-Cu-O films developed on MgO substrate always contained both the low T c Bi-2212 and high T c Bi-2223 phases [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the divergence of the crystallographic properties at the interface between YBCO and the commonly available substrates, as well as the difficulty to obtain chemical and structural properties compatible with the YBCO superconductor, constitute a great motivation to produce new optimal materials for this application. For example, MgO, the widely utilized substrate for YBCO thin films, produces an interlayer of barium salt at the YBCO-MgO interface, when the processing temperature is above 700 o C [5]. Another extensively used substrate for YBCO, LaAlO 3 , exhibits an excellent lattice coupling but has the disadvantage that it is available only as twinned single-crystal [4].…”
Section: Introductionmentioning
confidence: 99%